Sarcosaprophagous Diptera assemblages in natural habitats in central Spain: spatial and seasonal changes in composition (Medical and Veterinary Entomology, 2012)
The composition and spatial distribution of sarcosaprophagous Diptera assemblages were studied using carrion-baited traps along a bioclimatic gradient of natural habitats in central Spain throughout the different seasons during 1 year. Calliphoridae and Muscidae were the most abundant families, accounting for, respectively, 41.9% and 35.1% of all Diptera specimens collected. Other abundant families were Heleomyzidae (8.4%), Sarcophagidae (6.9%) and Piophilidae (5.1%). Fly assemblage compositions differed among bioclimatic levels, with Chrysomya albiceps (Wiedemann) (Diptera: Calliphoridae) being the dominant species in mesomediterranean habitats, Muscina levida (Harris) (Diptera: Muscidae) the dominant species in supramediterranean habitats, and Prochyliza nigrimana (Meigen) (Diptera: Piophilidae) the dominant species in oromediterranean habitats. Differences in assemblage composition were also found among seasons. Thermophobic species such as Calliphora vicina Robineau-Desvoidy (Diptera: Calliphoridae) and some species of Heleomyzidae were well represented during autumn, winter and spring in the three bioclimatic levels sampled. By contrast, thermophilic species such as Ch. albiceps and Lucilia sericata (Meigen) (Diptera: Calliphoridae) and most Muscidae and Sarcophagidae species were more abundant during summer and in mesomediterranean habitats located at lower elevations. Knowledge of the preferences of some species for certain habitats may be of ecological and forensic value and may establish a starting point for further research.

The SLOSS dilemma: A butterfly case study (BIODIVERSITY AND CONSERVATION, 1996)
Butterfly species richness is examined on simulated archipelagoes of 2, 3, 4 and 5 holm oak forest fragments in the Guadalajara Province (central Spain). It is shown that there are more species on several small `islands' than on a single island. Also, species number increases with the number of fragments that form the archipelago, and with the average distance between islands within the archipelago. Thus, we conclude, at least for butterflies in a system of fragmented helm oak forests in central Iberia, that the best strategy in order to maximize the conservation of species richness is the creation of a net of some small and scattered reserves.